2023
DOI: 10.3389/fpsyt.2022.1106004
|View full text |Cite
|
Sign up to set email alerts
|

Problematic Social Networking Site use-effects on mental health and the brain

Abstract: The association between excessive use of Social Networking Sites (SNS) and mental health is raising serious concern among health and education professionals. Problematic SNS use has been associated with an increased rate of depression, anxiety, stress, obsessive-compulsive disorder (OCD), attention-deficit/hyperactivity disorder (ADHD), and propensity to excessive alcohol use. It may also lead to vulnerability to aggression, cyberbullying and fear of missing out (FOMO). There is little evidence for cognitive i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
7
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 116 publications
0
7
0
1
Order By: Relevance
“…[35] concluded that ‘ … spending more than four hours per day … increased the probability of more adverse gaming significantly’ [35] (p. 5). There is corresponding evidence that this is the length of time per day that engagement with various forms of social media increases the risk of involvement that is pathological [36 ▪ ], although the nature of the content only partly overlaps.…”
Section: Hazardous Gamingmentioning
confidence: 99%
“…[35] concluded that ‘ … spending more than four hours per day … increased the probability of more adverse gaming significantly’ [35] (p. 5). There is corresponding evidence that this is the length of time per day that engagement with various forms of social media increases the risk of involvement that is pathological [36 ▪ ], although the nature of the content only partly overlaps.…”
Section: Hazardous Gamingmentioning
confidence: 99%
“…A recently published meta-analysis and literature review revealed the company Facebook, leader of the market, also owner of four companies Facebook, WhatsApp, Facebook-Messenger, and Instagram, in 2021, reported over 3.58 billion monthly users ( 1 ). Based on the extensive use of the above social networking sites, it is quite obvious to expect the potential risks involved in their systematic use.…”
mentioning
confidence: 99%
“…Unfortunately, for the most fragile among the users this easy connection can lead to excessive use, resulting in negative consequences on mental health, particularly social anxiety and depression. Systematic use of social networking sites may affect sleep quality and quantity, as well as altered emotional communication patterns ( 1 ).…”
mentioning
confidence: 99%
See 2 more Smart Citations